A Method of Resonant Series-parallel Identification. (2015) - Tkachenko, G.I.; Baklanov, A.N.
Abstract: This paper describes a method of resonant series-parallel identification of resistive-capacitive sensors parameters and the solution of the system object model that allows you to define its parameters, inaccessible to direct measurements. Computational experiments showed that the method of resonant series-parallel identification allows defining the parameters of RC-objects with distributed parameters. The proposed method has the following advantages: high speed while maintaining the desired accuracy of measurement and small error in calculations.